FAST NEUTRON IRRADIATION AND WALL EFFECT ANALYSIS IN THERMAL-HYDRAULICS ASPECT OF HTR-10MW AND PR-3000MW USING MODIFIED PEBBLE PROGRAM - El Bari, Bilal
Thermal-hydraulics aspect is one of the crucial aspects that must be considered when reactor design and operation analysis were performed, because this aspect involves security, safety, and efficiency factor that must have to be examined. In this study, thermal-hydraulics aspect of the HTR-10 type reactor was analyzed by reviewing the effects of fast wall effects and fast neutron irradiation using the PEBBLE program, the calculation. From the results which obtained from the program that taking into account of wall effect that induced porosity distribution, when the homogeneous porosity values is used, the value of temperature is tend to be inaccurate relatively to data reference alongside the wall of reactor core. The study concludes that either fast neutron irradiation or wall effect can induce the thermalhydraulics aspect of PBR core which is so important to be understanding more the safety ability of PBR core.